Analysis of the feasibility of early hospital discharge after autologous hematopoietic stem cell transplantation and the implications to nursing care - Barban,Alessandra (2014)
INTRODUCTION: Autologous hematopoietic stem cell transplantation is a conduct used to treat some hematologic diseases and to consolidate the treatment of others. In the field of nursing, the few published scientific studies on nursing care and early hospital discharge of transplant patients are deficient. Knowledge about the diseases treated using hematopoietic stem cell transplantation, providing guidance to patients and caregivers and patient monitoring are important nursing activities in this process. Guidance may contribute to long-term goals through patients' short-term needs.AIM: To analyze the results of early hospital discharge on the treatment of patients submitted to autologous transplantation and the influence of nursing care on this conduct.METHODS: A retrospective, quantitative, descriptive and transversal study was conducted. The hospital records of 112 consecutive patients submitted to autologous transplantation in the period from January to December 2009 were revisited. Of these, 12 patients, who remained in hospital for more than ten days after transplantation, were excluded from the study.RESULTS: The medical records of 100 patients with a median age of 48.5 years (19-69 years) were analyzed. All patients were mobilized and hematopoietic stem cells were collected by leukapheresis. The most common conditioning regimes were BU12Mel100 and BEAM 400. Toxicity during conditioning was easily managed in the outpatient clinic. Gastrointestinal toxicity, mostly Grades I and II, was seen in 69% of the patients, 62% of patients had diarrhea, 61% of the patients had nausea and vomiting and 58% had Grade I and II mucositis. Ten patients required hospitalization due to the conditioning regimen. Febrile neutropenia was seen in 58% of patients. Two patients died before Day +60 due to infections, one with aplasia. The median times to granulocyte and platelet engraftment were 12 days and 15 days, respectively, with median red blood cell and platelet transfusions until discharge of three and four units, respectively. Twenty-three patients required rehospitalization before being discharged from the outpatient clinic.CONCLUSION: The median time to granulocyte engraftment was 12 days and during the aplasia phase few patients were hospitalized or suffered infections. The toxicity of the conditioning was the leading cause of rehospitalization. The nursing staff participated by providing guidance to patients and during the mobilization, transplant and outpatient follow-up phases, thus helping to successfully manage toxicity.